THE INFLUENCE OF BRAND LOYALTY AND SERVICE QUALITY ON CONSUMER PURCHASE DECISIONS - Aidil Putra; Budianto (Journal of Financial Management & Accounting, 2024)
Brand loyalty (brand loyalty) is when consumers ask for a brand and will look anywhere to get the brand. Service quality is the superiority of a service that can only be assessed by customers. Purchasing decisions are a decision-making process in which consumers must first solve problems. This study uses multiple linear regression analysis methods to determine the relationship of each independent variable to the dependent variable. The population in this study were: all customers who have a policy age of more than 5 years, totaling 67 customers. The study used saturated samples so that the number of samples in this study was 67 respondents. The results of the simultaneous hypothesis test showed that Brand Loyalty and Service Quality had a significant effect on Purchasing Decisions. Partially, each Brand Loyalty and service quality had a significant effect on Purchasing Decisions. Keywords: Brand Loyalty, Service Quality, Purchase Decision